Nanomechanical properties of neutron-irradiated concrete - Ondřej Libera; Jiří Němeček; Patricie Halodová; Zbyněk Hlaváč; Jiří Němeček (Acta Polytechnica CTU Proceedings)
Concrete exposed to irradiation from nuclear reactor undergoes atomic-level degradation due to the influence of neutrons, secondary gamma rays, and associated gamma heating. The radiationinduced damage decreases the mechanical properties of the concrete and affects its performance as a construction material. The concrete samples analysed in this work were prepared from blended Portland cement CEM II 32.5R mixed with siliceous aggregates with a size of 0–2.5 mm. The material underwent irradiation in the LVR-15 research reactor in Research Centre Rež to the target neutron fluence of 1.6–1.8 · 1019 n cm−2 (E>0.1MeV) and received the gamma dose of ⁓ 500 MGy. The temperatures during irradiation were kept within a range of 50–60 °C. The mechanical properties of the individual phases in the cementitious matrix after neutron irradiation were assessed by the nanoindentation. To track the evolution of the nanomechanical properties of individual components under radiation, a comparison was made between the mechanical properties of neutron-irradiated material and pristine concrete.